On Categories of Fuzzy Petri Nets - Arun K. Srivastava; S. P. Tiwari (Advances in Fuzzy Systems)
We introduce the concepts of fuzzy Petri nets and marked fuzzy Petri nets along with their appropriate morphisms, which leads to two categories of such Petri nets. Some aspects of the internal structures of these categories are then explored, for example, their reflectiveness/coreflectiveness and symmetrical monoidal closed structure.